APPLICATIONS OF DIFFERENTIAL SUBORDINATION AND SUPERORDINATION - C. Ganesamoorthy; N. Marikkannan; M. P. Jeyaraman (IndoMS, 2008)
In the present investigation we obtain asndwich theorems for certain subclass of analytic functions defined by convolution. Our results generalizes several well known results.DOI : http://dx.doi.org/10.22342/jims.14.1.62.47-56